Situation Report: Romania, 8 August 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Salary Increase CSSR-Ukrainian-Romania Power Link Up Next Year Radiofication of Collective Farm Members['] Houses Romanian Party Delegation in Sofia Romanian Delegation at Journalists' Congress Romanian Navy Day Celebrations Cereal Harvesting Almost Finished Second Death at London Legation